Graphene full-biodegradable polyolefin composite material and preparation method thereof
By pretreating graphene oxide and melting blending with polyolefin, the problem of difficulty in taking into account the stability and biodegradation performance of polyolefin materials during the use period is solved, and the stability of graphene-fully biodegradable polyolefin composite materials is achieved. and efficient biodegradation.
Patent Information
- Application Number
- CN202411430659.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polyolefin plastic materials are difficult to maintain stability and biodegradable properties during their use period, resulting in environmental pollution problems.
The preparation method of graphene-fully biodegradable polyolefin composite material is adopted. The organic graft is formed by pretreating graphene oxide, which improves its compatibility with polyolefins, makes graphene evenly dispersed, and is bonded to the surface of graphene oxide. Branch polyolefins enhance biodegradability.
The material stability and safety during the use cycle are achieved, while improving the biodegradation rate and reducing the environmental pollution risk of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of preparation of environmentally degradable materials, and in particular to a graphene fully biodegradable polyolefin composite material and a preparation method thereof. Background Art
[0002] The plastic industry has developed rapidly, and its uses have penetrated into all areas of the national economy, with a wide range of uses. Most of the waste plastics produced in China each year are polypropylene (PP), polyethylene (PE) and polystyrene (PS) materials, which cannot be naturally decomposed. Therefore, if disposable plastic packaging waste made of PP materials, PE materials, and PS materials and their corresponding agricultural films and disposable tableware are discarded at will, they will accumulate on the land due to their non-degradability, thus causing serious white pollution. Moreover, this potential pollution will also increase with the increase in people's use and the accumulation of time. At present, my country's white pollution is serious, which has attracted widespread attention from relevant government departments and society. Relevant laws and regulations have been introduced, especially in the European and American markets, and the use of non-degradable plastics is strictly restricted.
[0003] Polyolefin plastics are a class of polymer materials with C–C bonds as their skeletons, and are widely used in various fields of daily life. Due to their stable chemical properties and difficulty in being rapidly degraded by microorganisms in the environment, polyolefin plastic waste continues to accumulate worldwide, causing serious environmental pollution and ecological crises. In recent years, the use of biological methods to degrade polyolefin plastics has attracted widespread attention from researchers. The abundant microbial resources in nature provide the possibility for biodegradation of polyolefin plastic waste, and some microorganisms with the ability to degrade polyolefin plastics have been reported one after another.
[0004] The degradation ability and stability during the service life of existing biodegradable plastics are often not well combined, and the two properties are easily offset by each other. Therefore, developing a biodegradable material with excellent comprehensive performance is an important direction of current research work. Summary of the invention
[0005] The purpose of the present application is to provide a method for preparing a graphene fully biodegradable polyolefin composite material, wherein graphene oxide is pretreated to form organic-grafted graphene oxide, which is then melt-blended with polyolefin, and polyolefin is grafted on the surface of the graphene oxide, thereby improving its compatibility with the polyolefin material, making the graphene uniformly dispersed in the matrix of the polyolefin without agglomeration, reducing the stacking of graphene sheets, and while stabilizing the structure of the composite material, the oxygen-containing functional groups on the graphene oxide are conducive to increasing the rate of biodegradation.
[0006] Another object of the present application is to provide a graphene fully biodegradable polyolefin composite material prepared by the above method, which has good stability and safety during its use period and also has good biodegradability.
[0007] The present application solves the technical problem by adopting the following technical solution.
[0008] On the one hand, the present invention provides a method for preparing a graphene fully biodegradable polyolefin composite material, comprising the following steps:
[0009] S1: Assemble a reaction bottle in an ice water bath, add concentrated sulfuric acid into the reaction bottle, and then add graphite powder and sodium nitrate while stirring to fully react;
[0010] S2: Add potassium permanganate to the reaction solution of S1 in portions while stirring. After reacting for 20-40 minutes, heat to 30-40°C, continue stirring for 30-40 minutes, then slowly add deionized water, continue stirring, and add hydrogen peroxide to make the solution turn bright yellow;
[0011] S3: filtering while hot, and washing with 3%-5% HCl solution and deionized water until no sulfate is detected in the filtrate, freeze-drying the filtered product to obtain graphene oxide, and storing it for later use;
[0012] S4: mixing graphene oxide and solvent in a mass volume ratio of 1g:200-1000mL, performing ultrasonic dispersion treatment at a temperature below the boiling point of the solvent, then adding organic matter, and passing nitrogen gas for reflux reaction. After the reaction is completed, the reaction solution is filtered, and the filter cake is repeatedly rinsed with excess ethanol and dried to obtain organic matter-grafted graphene oxide;
[0013] S5: The polyolefin-grafted graphene prepared in S4 and polyolefin are mixed in a weight ratio of (1-10):100, melt-blended in an internal mixer at 160-230° C. for 5-30 min, and then cooled, crushed or granulated to obtain a graphene-polyolefin composite material.
[0014] On the other hand, an embodiment of the present application provides a graphene fully biodegradable polyolefin composite material prepared by the above method.
[0015] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0016] 1. The embodiment of the present application provides a method for preparing a graphene fully biodegradable polyolefin composite material, wherein graphene oxide is pretreated to form organic-grafted graphene oxide, which is then melt-blended with polyolefin, and polyolefin is grafted on the surface of the graphene oxide, thereby improving its compatibility with the polyolefin material, making the graphene uniformly dispersed in the matrix of the polyolefin without agglomeration, reducing the stacking of graphene sheets, and stabilizing the structure of the composite material while the oxygen-containing functional groups on the graphene oxide are conducive to increasing the rate of biodegradation.
[0017] 2. The present application provides a graphene fully biodegradable polyolefin composite material prepared by the above method, which has good stability and safety during its use period and good biodegradability. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0019] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0020] The present invention provides a method for preparing a graphene fully biodegradable polyolefin composite material, comprising the following steps:
[0021] S1: Assemble a reaction bottle in an ice water bath, add concentrated sulfuric acid into the reaction bottle, and then add graphite powder and sodium nitrate while stirring to fully react;
[0022] S2: Add potassium permanganate to the reaction solution of S1 in portions while stirring. After reacting for 20-40 minutes, heat to 30-40°C, continue stirring for 30-40 minutes, then slowly add deionized water, continue stirring, and add hydrogen peroxide to make the solution turn bright yellow;
[0023] S3: filtering while hot, and washing with 3%-5% HCl solution and deionized water until no sulfate is detected in the filtrate, freeze-drying the filtered product to obtain graphene oxide, and storing it for later use;
[0024] S4: mixing graphene oxide and solvent in a mass volume ratio of 1g:200-1000mL, performing ultrasonic dispersion treatment at a temperature below the boiling point of the solvent, then adding organic matter, and passing nitrogen gas for reflux reaction. After the reaction is completed, the reaction solution is filtered, and the filter cake is repeatedly rinsed with excess ethanol and dried to obtain organic matter-grafted graphene oxide;
[0025] S5: The polyolefin-grafted graphene prepared in S4 and polyolefin are mixed in a weight ratio of (1-10):100, melt-blended in an internal mixer at 160-230° C. for 5-30 min, and then cooled, crushed or granulated to obtain a graphene-polyolefin composite material.
[0026] The concentrated sulfuric acid is a strong proton acid, which enters the graphite interlayer. Potassium permanganate is a strong oxidant to oxidize graphite, and the generated graphite oxide is subjected to ultrasonic exfoliation to obtain graphene oxide. In a strong acid environment, sodium nitrate has strong oxidizing properties. Hydrogen peroxide removes excess potassium permanganate in the oxidation, and oxidizes it into divalent manganese ions and removes it. Dilute hydrochloric acid washes away the metal ions and sulfate ions, and barium chloride is used to detect the sulfate ions.
[0027] Graphene oxide is pretreated to form organic-grafted graphene oxide, which is then melt-blended with polyolefin and grafted with polyolefin on the surface of graphene oxide, thereby improving its compatibility with polyolefin materials, making graphene uniformly dispersed in the matrix of polyolefin without agglomeration, reducing the stacking of graphene sheets, and stabilizing the structure of the composite material. At the same time, the oxygen-containing functional groups on the graphene oxide are conducive to increasing the rate of biodegradation.
[0028] The preparation of graphene-polyolefin composites uses internal mixer melt blending, which has the advantage that the requirements for raw material particle size and uniformity are not as strict as those for dry powder blending, so the raw material preparation operation is relatively simple. In the molten state, the molecules of different polymers are broken up and convection is intensified, and the strong shearing effect of the mixing equipment makes the mixing effect significantly higher than that of dry powder blending. In addition, it may form a part of grafted or block copolymers, thereby promoting compatibility between components.
[0029] In some embodiments of the present application, in the above S1, the mass ratio of graphite powder, concentrated sulfuric acid and sodium nitrate is 1:(8-12):(2-5). Concentrated sulfuric acid is a strong acid and provides hydrogen ions, and sodium nitrate provides nitrate ions, and nitrate ions have strong oxidizing properties in a strong acid environment. In order to fully oxidize the graphite powder, the amount of concentrated sulfuric acid and sodium nitrate must be sufficient, but too much should be avoided to cause waste.
[0030] In some embodiments of the present application, in the above S2, when potassium permanganate is added, the reaction temperature is controlled at 5°C-20°C. Since potassium permanganate is a strong oxidant, it will release a lot of heat when reacting with concentrated sulfuric acid during the addition process. The ice water bath can keep the reaction temperature below 20°C to avoid local overtemperature causing the reaction to run away. At the same time, the low temperature environment helps the reactants to mix better, ensuring that potassium permanganate can be evenly dispersed in sulfuric acid, thereby improving the consistency and efficiency of the reaction.
[0031] In some embodiments of the present application, in the above S2, the amount of potassium permanganate added is 3%-5% of the mass of graphite. Potassium permanganate reacts with graphite in an acidic medium to oxidize it into graphite oxide. In this process, potassium permanganate weakens the van der Waals force between graphite sheets, thereby gradually peeling off the layers. And through the selective edge modification of potassium permanganate, oxygen-containing functional groups such as carboxyl and epoxy groups can be introduced at the edge of graphene. This modification can change the electronic structure of graphene and improve its application performance in the fields of composite materials, sensors, catalysts, etc. However, the amount of potassium permanganate should not be added too much, otherwise more hydrogen peroxide will be needed in subsequent steps to remove potassium permanganate, causing waste.
[0032] In some embodiments of the present application, in the above S2, the amount of hydrogen peroxide added is 3%-8% of the mass of graphite. The purpose of hydrogen peroxide is to remove excess potassium permanganate in the system, so its amount should be proportional to the amount of potassium permanganate.
[0033] In some embodiments of the present application, the above-mentioned solvent is a mixture of one or more of dimethylformamide, xylene, toluene, carbon tetrachloride, water, alcohol, and acetone, and when there are multiple solvents, the components are mutually soluble.
[0034] In some embodiments of the present application, the organic substance is a mixture of one or more of octadecylamine, maleic anhydride, ethylene vinyl acetate, siloxane, and ethanolamine.
[0035] In some embodiments of the present application, in the above S4, the frequency of ultrasonic dispersion is 55-90 Hz and the time is 40-80 min. Ultrasound can make graphene oxide dispersed more evenly in the solvent to avoid stacking. The frequency of ultrasound should not be too high and the time should not be too long, which will cause the temperature of the solution to rise during the ultrasonic process. If it is higher than the boiling point of the solvent, it will cause the solvent to evaporate. At the same time, if the ultrasonic frequency is too low and the time is too short, the graphene oxide will not be dispersed evenly enough.
[0036] In some embodiments of the present application, the polyolefin is selected from any one of polyethylene, polyvinyl chloride, polypropylene, ethylene-vinyl acetate copolymer, and ethylene-methyl acrylate copolymer.
[0037] The embodiment of the present application provides a graphene fully biodegradable polyolefin composite material prepared by the above method.
[0038] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0039] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to specific embodiments.
[0040] Example 1
[0041] The present invention provides a method for preparing a graphene fully biodegradable polyolefin composite material, comprising the following steps:
[0042] S1: Assemble a reaction bottle in an ice water bath, add concentrated sulfuric acid into the reaction bottle, and then add graphite powder and sodium nitrate while stirring to fully react, wherein the mass ratio of graphite powder, concentrated sulfuric acid and sodium nitrate is 1:8:2;
[0043] S2: Add potassium permanganate to the reaction solution of S1 in portions while stirring, wherein the amount of potassium permanganate added is 3% of the mass of graphite, and the temperature is controlled at 5°C during the reaction. After reacting for 20 minutes, raise the temperature to 30°C, continue stirring for 30 minutes, then slowly add deionized water, continue stirring, and add hydrogen peroxide at 3% of the mass of graphite to make the solution turn bright yellow;
[0044] S3: Filter while hot, and wash with 3% HCl solution and deionized water until no sulfate is detected in the filtrate, freeze-dry the filtered product to obtain graphene oxide, and store it for later use;
[0045] S4: Graphene oxide and dimethylformamide are mixed in a mass volume ratio of 1g:200mL, and ultrasonic dispersion is performed at a temperature below the boiling point of the solvent. The frequency of ultrasonic dispersion is 55Hz and the time is 80min. Then, octadecylamine is added, and nitrogen is passed through for reflux reaction. After the reaction is completed, the reaction solution is filtered, and the filter cake is repeatedly rinsed with excess ethanol and dried to obtain organic-grafted graphene oxide;
[0046] S5: The polyolefin-grafted graphene prepared in S4 and polyethylene are mixed in a weight ratio of 1:100, melt-blended in an internal mixer at 160° C. for 30 minutes, and then cooled, crushed or granulated to obtain a graphene-polyolefin composite material.
[0047] Example 2
[0048] The present invention provides a method for preparing a graphene fully biodegradable polyolefin composite material, comprising the following steps:
[0049] S1: Assemble a reaction bottle in an ice water bath, add concentrated sulfuric acid into the reaction bottle, and then add graphite powder and sodium nitrate while stirring to fully react, wherein the mass ratio of graphite powder, concentrated sulfuric acid and sodium nitrate is 1:12:5;
[0050] S2: Add potassium permanganate to the reaction solution of S1 in portions while stirring, wherein the amount of potassium permanganate added is 5% of the mass of graphite, and the temperature is controlled at 20°C during the reaction. After reacting for 40 minutes, raise the temperature to 40°C, continue stirring for 40 minutes, then slowly add deionized water, continue stirring, and add hydrogen peroxide at 8% of the mass of graphite to make the solution turn bright yellow;
[0051] S3: Filter while hot, and wash with 5% HCl solution and deionized water until no sulfate is detected in the filtrate, freeze-dry the filtered product to obtain graphene oxide, and store it for later use;
[0052] S4: Graphene oxide and acetone are mixed at a mass volume ratio of 1g:1000mL, and ultrasonic dispersion is performed at a temperature below the boiling point of the solvent. The frequency of ultrasonic dispersion is 90Hz and the time is 40min. Maleic anhydride is then added, and nitrogen is passed through for reflux reaction. After the reaction is completed, the reaction solution is filtered, and the filter cake is repeatedly rinsed with excess ethanol and dried to obtain organic-grafted graphene oxide;
[0053] S5: The polyolefin-grafted graphene prepared in S4 and polypropylene are mixed in a weight ratio of 10:100, melt-blended in an internal mixer at 230° C. for 5 minutes, and then cooled, crushed or granulated to obtain a graphene-polyolefin composite material.
[0054] Example 3
[0055] The present invention provides a method for preparing a graphene fully biodegradable polyolefin composite material, comprising the following steps:
[0056] S1: Assemble a reaction bottle in an ice water bath, add concentrated sulfuric acid into the reaction bottle, and then add graphite powder and sodium nitrate while stirring to fully react, wherein the mass ratio of graphite powder, concentrated sulfuric acid and sodium nitrate is 1:10:3;
[0057] S2: Add potassium permanganate to the reaction solution of S1 in portions while stirring, wherein the amount of potassium permanganate added is 4% of the mass of graphite, and the temperature is controlled at 15°C during the reaction. After reacting for 30 minutes, raise the temperature to 35°C, continue stirring for 35 minutes, then slowly add deionized water, continue stirring, and add 5% hydrogen peroxide by mass of graphite to make the solution turn bright yellow;
[0058] S3: Filter while hot, and wash with 4% HCl solution and deionized water until no sulfate is detected in the filtrate, freeze-dry the filtered product to obtain graphene oxide, and store it for later use;
[0059] S4: Graphene oxide and xylene are mixed in a mass volume ratio of 1g:400mL, and ultrasonic dispersion is performed at a temperature below the boiling point of the solvent. The frequency of ultrasonic dispersion is 65Hz and the time is 50min. Then, siloxane is added, and nitrogen is passed through for reflux reaction. After the reaction is completed, the reaction liquid is filtered, and the filter cake is repeatedly rinsed with excess ethanol and dried to obtain organic-grafted graphene oxide;
[0060] S5: The polyolefin-grafted graphene prepared in S4 and polyvinyl chloride are mixed in a weight ratio of 3:100, melt-blended in an internal mixer at 180° C. for 15 minutes, and then cooled, crushed or granulated to obtain a graphene-polyolefin composite material.
[0061] Example 4
[0062] The present invention provides a method for preparing a graphene fully biodegradable polyolefin composite material, comprising the following steps:
[0063] S1: Assemble a reaction bottle in an ice water bath, add concentrated sulfuric acid into the reaction bottle, and then add graphite powder and sodium nitrate while stirring to fully react, wherein the mass ratio of graphite powder, concentrated sulfuric acid and sodium nitrate is 1:9:3;
[0064] S2: Add potassium permanganate to the reaction solution of S1 in portions while stirring, wherein the amount of potassium permanganate added is 3.5% of the mass of graphite, and the temperature is controlled at 10°C during the reaction. After reacting for 35 minutes, raise the temperature to 35°C, continue stirring for 40 minutes, then slowly add deionized water, continue stirring, and add 7% hydrogen peroxide by mass of graphite to make the solution turn bright yellow;
[0065] S3: Filter while hot, and wash with 3.5% HCl solution and deionized water until no sulfate is detected in the filtrate, freeze-dry the filtered product to obtain graphene oxide, and store it for later use;
[0066] S4: Graphene oxide and carbon tetrachloride are mixed in a mass volume ratio of 1g:250mL, and ultrasonic dispersion is performed at a temperature below the boiling point of the solvent. The frequency of ultrasonic dispersion is 80Hz and the time is 45min. Then, ethanolamine is added and nitrogen is passed through for reflux reaction. After the reaction is completed, the reaction solution is filtered, and the filter cake is repeatedly rinsed with excess ethanol and dried to obtain organic-grafted graphene oxide;
[0067] S5: The polyolefin grafted graphene prepared in S4 and ethylene-vinyl acetate copolymer are mixed in a weight ratio of 7:100, melt-blended in an internal mixer at 200° C. for 25 minutes, and then cooled, crushed or granulated to obtain a graphene-polyolefin composite material.
[0068] Example 5
[0069] The present invention provides a method for preparing a graphene fully biodegradable polyolefin composite material, comprising the following steps:
[0070] S1: Assemble a reaction bottle in an ice water bath, add concentrated sulfuric acid into the reaction bottle, and then add graphite powder and sodium nitrate while stirring to fully react, wherein the mass ratio of graphite powder, concentrated sulfuric acid and sodium nitrate is 1:11:4.5;
[0071] S2: Add potassium permanganate to the reaction solution of S1 in portions while stirring, wherein the amount of potassium permanganate added is 4.5 of the mass of graphite, and the temperature is controlled at 15°C during the reaction. After reacting for 35 minutes, raise the temperature to 35°C, continue stirring for 30-40 minutes, then slowly add deionized water, continue stirring, and add 4% hydrogen peroxide by mass of graphite to make the solution turn bright yellow;
[0072] S3: Filter while hot, and wash with 3.5% HCl solution and deionized water until no sulfate is detected in the filtrate, freeze-dry the filtered product to obtain graphene oxide, and store it for later use;
[0073] S4: Graphene oxide and alcohol are mixed at a mass volume ratio of 1g:500mL, and ultrasonic dispersion is performed at a temperature below the boiling point of the solvent. The frequency of ultrasonic dispersion is 75Hz and the time is 65min. Then, ethanolamine is added and nitrogen is passed through for reflux reaction. After the reaction is completed, the reaction solution is filtered, and the filter cake is repeatedly rinsed with excess ethanol and dried to obtain organic-grafted graphene oxide;
[0074] S5: The polyolefin grafted graphene prepared in S4 and ethylene-methyl acrylate copolymer are mixed in a weight ratio of 9:100, melt-blended in an internal mixer at 220° C. for 25 minutes, and then cooled, crushed or granulated to obtain a graphene-polyolefin composite material.
[0075] Comparative Example 1
[0076] Commercially available polypropylene material, brand: LyondellBasell, product specification: HP371P, specification: 371mm.
[0077] Comparative Example 2
[0078] This comparative example provides a method for preparing a graphene fully biodegradable polyolefin composite material, comprising the following steps:
[0079] S1: Assemble a reaction bottle in an ice water bath, add concentrated sulfuric acid into the reaction bottle, and then add graphite powder and sodium nitrate while stirring to fully react, wherein the mass ratio of graphite powder, concentrated sulfuric acid and sodium nitrate is 1:10:3;
[0080] S2: Add potassium permanganate to the reaction solution of S1 in portions while stirring, wherein the amount of potassium permanganate added is 4% of the mass of graphite, and the temperature is controlled at 15°C during the reaction. After reacting for 30 minutes, raise the temperature to 35°C, continue stirring for 35 minutes, then slowly add deionized water, continue stirring, and add 5% hydrogen peroxide by mass of graphite to make the solution turn bright yellow;
[0081] S3: Filter while hot, and wash with 4% HCl solution and deionized water until no sulfate is detected in the filtrate, freeze-dry the filtered product to obtain graphene oxide, and store it for later use;
[0082] S4: The graphene oxide prepared in S3 and polyvinyl chloride are mixed in a weight ratio of 3:100, melt-blended in an internal mixer at 180° C. for 15 minutes, and then cooled, crushed or granulated to obtain a graphene-polyolefin composite material.
[0083] Experimental Example 1
[0084] The change of mechanical properties of samples due to degradation is evaluated by the retention rate of tensile strength and elongation at break. The lower the retention rate of tensile strength and elongation at break of the sample after degradation, the greater the degree of performance degradation of the sample after degradation, that is, the better the degradation performance. It is generally believed that when the retention rate of elongation at break is greater than 80%, it is the induction period, that is, the period when the product's use value is realized; when the retention rate of elongation at break is less than 80% and greater than 20%, it is the aging period, and the use performance decreases; when the retention rate of elongation at break is less than 20%, it is the brittle period, and its use performance is completely lost.
[0085] The fully biodegradable materials prepared in Examples 1-5 and Comparative Examples 1-2 were tested under normal storage conditions (no adjacent heat source, no direct sunlight, no direct rain), wherein the tensile strength and elongation at break were tested in accordance with GB / T1040.3-2006, the sample used was type 2, the length was 150 mm, the width was 15 mm, and the test speed was 200 mm / min. The data in the longitudinal (MD) and transverse (TD) directions of the sample were detected. The test results of the tensile strength retention rate after curing for two days, one month, six months, and one year are shown in Table 1, and the test results of the elongation at break after curing for two days, one month, six months, and one year are shown in Table 2.
[0086] Table 1. Test results of tensile strength retention rate
[0087]
[0088] Table 2. Test results of elongation at break
[0089]
[0090]
[0091] It can be seen from Table 1 and Table 2 that the fully biodegradable materials prepared in Examples 1-5 have a tensile strength retention rate and elongation at break greater than 90% within one year, which is basically consistent with the ordinary polyolefin materials in Comparative Example 1, indicating that the fully biodegradable materials prepared in Examples 1-5 of the present application are not degraded after being stored in an ordinary storage environment for one year. This ensures the safety and stability of normal use, indicating that the graphene and polyolefin composite can have good full biodegradability after one year while ensuring stability within the service life.
[0092] The difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the graphene oxide is not pretreated to form organic-grafted graphene oxide, but the graphene oxide is directly melt-blended with the polyolefin, which causes the graphene oxide to agglomerate and is not well compatible with the polyolefin. Therefore, the full biodegradability after one year is not as good as that of the sample prepared in Example 3.
[0093] Experimental Example 2
[0094] The soil burial test is a method for evaluating the biodegradability of materials. It evaluates the biodegradability of materials by burying them in the soil and monitoring their changes over time. This method buries the material in the soil to simulate the soil environment under natural conditions, and evaluates its biodegradation rate by observing the degradation of the material in the soil. Test standards such as GB / T22047.
[0095] Operation steps of soil burial test
[0096] 1. Prepare test materials: Select a sample of appropriate size and ensure that the surface is flat and free of contamination.
[0097] 2. Digging trenches: Dig trenches in the soil to be investigated to a depth equivalent to the depth of the soil in use.
[0098] 3. Placement of samples: Place the samples prepared in the usual manner at the specified horizontal depths, and then backfill the soil as per the technical requirements for testing.
[0099] 4. Burial requirements: The samples must be buried at the same depth and covered with soil of the same thickness.
[0100] 5. Monitoring and recording: Regularly monitor the degradation of materials and record the changes in the material mass, the original mass m, and the remaining mass m' after 180 days of degradation.
[0101] 6. Data analysis: Calculation of degradation rate, degradation rate = (m-m') × 100%.
[0102] The degradation rate test results of the fully biodegradable materials prepared in Examples 1-5 and Comparative Examples 1-2 are shown in Table 3:
[0103] Table 3. Degradation rate test results
[0104] Group Degradation rate (%) Example 1 36.8% Example 2 37.2% Example 3 38.2% Example 4 39.6% Example 5 40.1% Comparative Example 1 8.2% Comparative Example 2 11.1%
[0105] As shown in Table 3, compared with the common polyolefin materials in Comparative Example 1, the fully biodegradable materials prepared in Examples 1-5 have a very high biodegradation rate. When buried in the soil, the degradation rate is as high as 40.1% in half a year, and the biodegradability is excellent. The degradation rate of the sample in Comparative Example 2 corresponds to the result of Experiment 1.
[0106] In summary, the embodiments of the present application provide a method for preparing a graphene fully biodegradable polyolefin composite material, wherein graphene oxide is pretreated to form organic-grafted graphene oxide, which is then melt-blended with polyolefin, and polyolefin is grafted on the surface of the graphene oxide, thereby improving its compatibility with the polyolefin material, making the graphene uniformly dispersed in the matrix of the polyolefin without agglomeration, reducing the stacking of graphene sheets, and stabilizing the structure of the composite material while the oxygen-containing functional groups on the graphene oxide are conducive to increasing the rate of biodegradation.
[0107] The embodiment of the present application provides a graphene fully biodegradable polyolefin composite material prepared by the above method, which has good stability and safety during its use period and also has good biodegradability.
[0108] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0109] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or plural, respectively.
[0110] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a graphene fully biodegradable polyolefin composite material, characterized in that: The following steps are involved: S1: Assemble a reaction bottle in an ice water bath, add concentrated sulfuric acid into the reaction bottle, and then add graphite powder and sodium nitrate while stirring to fully react; S2: Add potassium permanganate to the reaction solution of S1 in portions while stirring. After reacting for 20-40 minutes, heat to 30-40°C, continue stirring for 30-40 minutes, then slowly add deionized water, continue stirring, and add hydrogen peroxide to make the solution turn bright yellow; S3: filtering while hot, and washing with 3%-5% HCl solution and deionized water until no sulfate is detected in the filtrate, freeze-drying the filtered product to obtain graphene oxide, and storing it for later use; S4: mixing graphene oxide and solvent in a mass volume ratio of 1g:200-1000mL, performing ultrasonic dispersion treatment at a temperature below the boiling point of the solvent, then adding organic matter, and passing nitrogen gas for reflux reaction. After the reaction is completed, the reaction solution is filtered, and the filter cake is repeatedly rinsed with excess ethanol and dried to obtain organic matter-grafted graphene oxide; S5: The polyolefin-grafted graphene prepared in S4 and polyolefin are mixed in a weight ratio of (1-10):100, melt-blended in an internal mixer at 160-230° C. for 5-30 min, and then cooled, crushed or granulated to obtain a graphene-polyolefin composite material.
2. The method for preparing a graphene fully biodegradable polyolefin composite material according to claim 1, characterized in that: In S1, the mass ratio of graphite powder, concentrated sulfuric acid and sodium nitrate is 1:(8-12):(2-5).
3. The method for preparing a graphene fully biodegradable polyolefin composite material according to claim 1, characterized in that: In S2, when potassium permanganate is added, the reaction temperature is controlled at 5°C-20°C.
4. The method for preparing a graphene fully biodegradable polyolefin composite material according to claim 1, characterized in that: In the S2, the added amount of potassium permanganate is 3%-5% of the mass of graphite.
5. The method for preparing a graphene fully biodegradable polyolefin composite material according to claim 1, characterized in that: In the S2, the amount of hydrogen peroxide added is 3%-8% of the mass of graphite.
6. The method for preparing a graphene fully biodegradable polyolefin composite material according to claim 1, characterized in that: The solvent is a mixture of one or more of dimethylformamide, xylene, toluene, carbon tetrachloride, water, alcohol, and acetone, and when there are multiple solvents, the components are mutually soluble.
7. The method for preparing a graphene fully biodegradable polyolefin composite material according to claim 1, characterized in that: The organic matter is a mixture of one or more of octadecylamine, maleic anhydride, ethylene-vinyl acetate, siloxane and ethanolamine.
8. The method for preparing a graphene fully biodegradable polyolefin composite material according to claim 1, characterized in that: In S4, the frequency of ultrasonic dispersion is 55-90 Hz and the time is 40-80 min.
9. The method for preparing a graphene fully biodegradable polyolefin composite material according to claim 1, characterized in that: The polyolefin is selected from any one of polyethylene, polyvinyl chloride, polypropylene, ethylene-vinyl acetate copolymer, and ethylene-methyl acrylate copolymer.
10. A graphene fully biodegradable polyolefin composite material prepared by the preparation method according to any one of claims 1 to 9.